2012
DOI: 10.1017/s0007114512003777
|View full text |Cite
|
Sign up to set email alerts
|

The prebiotic effect ofAnoectochilus formosanusand its consequences on bone health

Abstract: The present study evaluated the prebiotic effect of a standardised aqueous extract of Anoectochilus formosanus (SAEAF) and its effects on osteoporosis in ovariectomised (OVX) rats. The OVX rats were randomly divided into five groups and orally treated with water, SAEAF (200 and 400 mg/kg daily) and inulin (400 mg/kg daily) for 12 weeks. The sham group was orally treated with water. The SAEAF treatment enhanced the number of faecal bifidobacteria in OVX rats. The results of a Ca-balance experiment showed that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…Similarly, GOS dose dependently increased rat tibia and femur strength (44,45). In addition, Anoecthochilus formosanus , a prebiotic herb, and inulin also increase bone strength in 12-week-old OVX rats (46). This effect on bone strength was observed in the absence of a significant change in bone volume, suggesting that prebiotics could change the extracellular matrix material properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, GOS dose dependently increased rat tibia and femur strength (44,45). In addition, Anoecthochilus formosanus , a prebiotic herb, and inulin also increase bone strength in 12-week-old OVX rats (46). This effect on bone strength was observed in the absence of a significant change in bone volume, suggesting that prebiotics could change the extracellular matrix material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Models for how prebiotics could increase calcium absorption include the involvement of fermentation of the prebiotics to release SCFA. It has been demonstrated that many prebiotic fibers (i.e., soluble corn fiber or fiber dextrin, inulin, FOS, agave fructans) increase the cecal content of SCFA such as acetate, propionate, butyrate, isobutyrate, valerate and isovalerate (23,34,46). SCFA can affect calcium absorption via two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anoectochilus genus such as Anoectochilus roxburghii, Anoectochilus formosanus, Anoectochilus elwesii, and Anoectochilus setaceus are used widespread in China, Vietnam, Sri Lanka, and Taiwan because of their medicinal properties (Yang, Wu, Lu, & Lin, 2013). They have remarkable curative effects of clearing heat and cooling blood, removing dampness, detoxification, antioxidative stress (Shih, Wu, & Lin, 2002; Wang et al., 2005), and anti‐inflammation (Hsieh, Hsiao, & Lin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A. formosanus exhibits hepatoprotective activity [1], antitumor and immunomodulatory effects [2, 3], asthma treatment effects [4], antihyperglycemic activity [5], prebiotic effects [6], and antiosteoporosis activity [7, 8]. The polysaccharide isolated from A. formosanus juice is a type II arabinogalactan with an average molecular weight of 29 kDa, and it is a prebiotic that increases the growth of probiotics in vivo and in vitro [6].…”
Section: Introductionmentioning
confidence: 99%